Reduced LIMK2 expression in colorectal cancer reflects its role in limiting stem cell proliferation. - Lourenço, F; Munro, J; Brown, J; Cordero, J; Stefanatos, R; Strathdee, K; Orange, C; Feller, S; Sansom, O; Vidal, M; Murray, G; Olson, M (2014)
OBJECTIVE: Colorectal cancer (CRC) is a major contributor to cancer mortality and morbidity. LIM kinase 2 (LIMK2) promotes tumour cell invasion and metastasis. The objectives of this study were to determine how LIMK2 expression is associated with CRC progression and patient outcome, and to use genetically modified Drosophila and mice to determine how LIMK2 deletion affects gastrointestinal stem cell regulation and tumour development. DESIGN: LIMK2 expression and activity were measured by immunostaining tumours from CRC-prone mice, human CRC cell lines and 650 human tumours. LIMK knockdown in Drosophila or Limk2 deletion in mice allowed for assessment of their contributions to gastrointestinal stem cell homeostasis and tumour development. RESULTS: LIMK2 expression was reduced in intestinal tumours of cancer-prone mice, as well as in human CRC cell lines and tumours. Reduced LIMK2 expression and substrate phosphorylation were associated with shorter patient survival. Genetic analysis in Drosophila midgut and intestinal epithelial cells isolated from genetically modified mice revealed a conserved role for LIMK2 in constraining gastrointestinal stem cell proliferation. Limk2 deletion increased colon tumour size in a colitis-associated colorectal mouse cancer model. CONCLUSIONS: This study revealed that LIMK2 expression and activity progressively decrease with advancing stage, and supports the hypothesis that there is selective pressure for reduced LIMK2 expression in CRC to relieve negative constraints imposed upon gastrointestinal stem cells.